2019
DOI: 10.3389/fendo.2019.00286
|View full text |Cite
|
Sign up to set email alerts
|

Tanycyte Gene Expression Dynamics in the Regulation of Energy Homeostasis

Abstract: Animal survival relies on a constant balance between energy supply and energy expenditure, which is controlled by several neuroendocrine functions that integrate metabolic information and adapt the response of the organism to physiological demands. Polarized ependymoglial cells lining the floor of the third ventricle and sending a single process within metabolic hypothalamic parenchyma, tanycytes are henceforth described as key components of the hypothalamic neural network controlling energy balance. Their str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 137 publications
(267 reference statements)
1
44
0
Order By: Relevance
“…TSH dependency of T3 production has been supported by in vitro and in vivo studies but was only recently incorporated into a model of hypothalamic-pituitary-thyroid regulation. 33 Because intracellular T3 concentrations are not readily measurable in humans, intracellular T3-regulating processes were not directly observable. Mathematically connecting chains of physiological events may generate unforeseen hypotheses, which then can be clinically assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSH dependency of T3 production has been supported by in vitro and in vivo studies but was only recently incorporated into a model of hypothalamic-pituitary-thyroid regulation. 33 Because intracellular T3 concentrations are not readily measurable in humans, intracellular T3-regulating processes were not directly observable. Mathematically connecting chains of physiological events may generate unforeseen hypotheses, which then can be clinically assessed.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Central regulation involving TRH and tanycytes is also incompletely understood and could only be partly implemented. 33 Because intracellular T3 concentrations are not readily measurable in humans, intracellular T3-regulating processes were not directly observable. 34 While our approach integrates central and local control, thereby denying an autonomy exclusively assigned to local control elements, it does not diminish the importance of their modulatory role in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the complete characterization of the different tanycyte subgroups is needed. While this classification currently defines 4 subgroups with specific markers for each of them, recent advances clearly showed that > 4 subgroups may be defined (see review [4]). In addition, according to their location along the ventricle wall, tanycytes likely interact with different neural cell types and different neuronal populations: this variable "connectivity" certainly has an impact on their transcriptomic profiles resulting in different subgroups with different functions.…”
Section: Future Improvements and Applicationsmentioning
confidence: 99%
“…Since their characterization by Horstmann [1], tanycytes are now considered as key cells in the regulation of numerous physiological functions, ranging from reproduction to energy balance [2][3][4]. Elongated unipolar ependymoglial cells lining the bottom and the lateral wall of the third ventricle, they send a long radial process to connect blood-brain barrier capillaries in the mediobasal hy-pothalamus and the fenestrated capillaries of the hypothalamo-hypophysial portal system in the median eminence [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation